A comprehensive review of the role of bone marrow biopsy and PET-CT in the evaluation of bone marrow involvement in adults newly diagnosed with DLBCL - Alyamany, Ruah; El Fakih, Riad; Alnughmush, Ahmed; Albabtain, Abdulwahab; Kharfan-Dabaja, Mohamed A.; Aljurf, Mahmoud (Frontiers in Oncology, 2024)
Diffuse large B cell lymphoma (DLBCL) is one of the most prevalent subtypes of non-Hodgkin lymphoma (NHL) and is known for commonly infiltrating extra-nodal sites. The involvement of the bone marrow by lymphoma cells significantly impacts the staging, treatment, and prognosis among the extra-nodal sites in DLBCL. Bone marrow biopsy has been considered the standard diagnostic procedure for detecting bone marrow involvement. However, advancements in imaging techniques, such as positron emission tomography-computed tomography (PET-CT), have shown an improved ability to detect bone marrow involvement, making the need for bone marrow biopsy debatable. This review aims to emphasize the importance of bone marrow evaluation in adult patients newly diagnosed with DLBCL and suggest an optimal diagnostic approach to identify bone marrow involvement in these patients.